2008
DOI: 10.1111/j.1467-9450.2008.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in facial imitation and verbally reported emotional contagion from spontaneous to emotionally regulated processing levels

Abstract: Previous studies on gender differences in facial imitation and verbally reported emotional contagion have investigated emotional responses to pictures of facial expressions at supraliminal exposure times. The aim of the present study was to investigate how gender differences are related to different exposure times, representing information processing levels from subliminal (spontaneous) to supraliminal (emotionally regulated). Further, the study aimed at exploring correlations between verbally reported emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 72 publications
9
45
1
1
Order By: Relevance
“…This finding suggests that facial mimicry in response to unpleasant expressions is not influenced by the arousal level of the expression. Because the stimuli used for high-and low-arousal unpleasant expressions could be described as "angry" and "sad" according to categorical choices (Fujimura and Suzuki, 2007), our results are consistent with previous studies reporting comparable EMG activity in response to angry and sad expressions (Lundqvist and Dimberg, 1995;Sonnby-Borgström et al, 2008). These data suggest that low-arousal of emotion notwithstanding, sad facial expressions have potential for facial mimicry comparable with angry expressions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding suggests that facial mimicry in response to unpleasant expressions is not influenced by the arousal level of the expression. Because the stimuli used for high-and low-arousal unpleasant expressions could be described as "angry" and "sad" according to categorical choices (Fujimura and Suzuki, 2007), our results are consistent with previous studies reporting comparable EMG activity in response to angry and sad expressions (Lundqvist and Dimberg, 1995;Sonnby-Borgström et al, 2008). These data suggest that low-arousal of emotion notwithstanding, sad facial expressions have potential for facial mimicry comparable with angry expressions.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies found comparable facial EMG activity in response to sad and angry facial expressions (Lundqvist and Dimberg, 1995;Sonnby-Borgström et al, 2008). Sad facial expressions are normally thought to indicate low arousal levels (Russell and Bullock, 1985), and hence these data suggest that high-and low-arousal unpleasant expressions have similar potential for facial mimicry.…”
Section: Introductionmentioning
confidence: 53%
“…Previous research supported that women have a higher propensity to congruently respond to emotional stimuli, a phenomenon that was verified in laboratory studies, resorting to facial expressions of emotion (Lundqvist, 2008;SonnbyBorgström, Jönsson, & Svenson, 2008). In our study we found that this tendency also prevailed with vocal stimuli, since the tendency to mimic the other was more prevalent and constant in the women group than in the men group,…”
supporting
confidence: 69%
“…They respond more rapidly and accurately, for example, to facial expressions of others and are particularly incisive in detecting emotions (e.g. SonnbyBorgström et al, 2008). However, to our knowledge, this natural tendency had never before been tested in vocal interactions, in a natural context.…”
mentioning
confidence: 99%
“…In relation to what each article defines as mimicry, time limits varied considerably and these time limits appear to be relevant for the identification of gender differences. For instance, Sonnby-Borgström (2002) first identified gender differences in facial mimicry at the automatic level between 17 ms and 30/40 ms; however, in a later more thorough, gender-specific investigation, Sonnby-Borgström et al (2008) revised this time frame having only demonstrated gender differences (in favour of females) at the supraliminal level (2,500 ms). A later study by Hermans et al (2009) employed a mimicry time limit of 1,500 ms and also found significant differences in favour of females.…”
Section: Stimulus Exposure Lengthmentioning
confidence: 99%